Active learning methodology, associated to formative assessment, improved cardiac physiology knowledge and decreased pre-test stress and anxiety - Cardozo, Lais Tono; Lima, Patricia Oliveira de; Carvalho, Maeline Santos Morais; Casale, Karina Reche; Bettioli, Ana Luisa; Azevedo, Maria Antonia Ramos de; Marcondes, Fernanda Klein (Frontiers in Physiology, 2023)
Stress and anxiety caused by assessments are often related to the student's insecurity regarding the knowledge to be evaluated, while teaching strategies that increase effective learning can assist in reducing it. The aim of this study was to evaluate the hypothesis that the use of an active methodology, associated to formative assessment, could reduce students' anxiety and stress, when compared to the traditional method, by promoting greater learning. New students enrolled in the same discipline of a Dentistry course were invited to participate in the study and were divided into two groups: traditional method and active methodology. The traditional method group received two lectures, delivered orally. The active methodology group received a lecture about cardiac cells and the autonomic control of cardiac function, with home study of the cardiac cycle using a textbook. In the second class, an individual formative assessment was applied. Afterwards, a group activity was performed with an educational game about the cardiac cycle, followed by a group formative assessment. After applying the traditional or active methodology, test 1 was carried out. Immediately before this test, saliva samples were collected for determination of the concentrations of the stress biomarkers cortisol and αamylase. The students also answered the State-Trait Anxiety Inventory questionnaire, used for anxiety level determination. The score obtained in the test 1 was significantly higher for the active methodology group, compared to the traditional method group. No significant differences between the groups were observed for baseline cortisol and salivary α-amylase concentrations, or for anxiety scores. Before test 1, traditional method group presented higher concentrations of salivary cortisol and α-amylase, compared to the respective baseline values, while the active methodology group showed no difference between the baseline and test 1 levels. Before test 1, there were increases in anxiety levels, relative to the respective baseline values, regardless of the teaching methodology used, but this increase was greater for the traditional method group, compared to the active methodology group. These results showed that the active methodology, associated to formative assessment, decreased test stress and anxiety, with improved student performance in comparison to traditional lectures.